Can Mucosal Healing Be a Cost-effective Endpoint for Biologic Therapy in Crohnʼs Disease? A Decision Analysis - Ashwin N. Ananthakrishnan; Joshua R. Korzenik; Chin Hur (2012)
Observational studies have demonstrated that mucosal healing (MH) may be associated with reductions in hospitalizations and surgeries for moderate to severe Crohn's disease (CD). Whether treatment to achieve MH is a cost-effective endpoint has not been established previously.We constructed a decision analytic model comparing two treatment strategies. In the clinical response (CR) arm, patients not in clinical remission at year 1 are dose-escalated. In the MH arm, patients with persistence of mucosal ulcerations at year 1 are escalated irrespective of clinical symptoms. Patients remain at risk for hospitalization and surgeries while they have active disease. We examined a 2-year time horizon.In the base case the MH strategy was more effective at 2 years (quality-adjusted life year [QALY] 0.71) compared to the CR strategy (QALY 0.69) but was also more expensive with an incremental cost-effectiveness ratio (ICER) of $49,278/QALY gained. In a hypothetical cohort of 100,000 patients assigned to each treatment arm, the MH strategy resulted in lower rates of hospitalization and surgery with a number needed to treat of 27 and 106, respectively. The results were sensitive to the ability of infliximab to achieve MH and the incremental benefit of MH over clinical remission.We demonstrate that MH as an endpoint is a cost-effective strategy in CD patients initiating IFX therapy. Further prospective studies on durability of MH and its incremental benefit as well as the ability of other available biologic agents to achieve MH are necessary to validate our findings.